Framing Mass Hysteria Covid-19 dalam Berita Tempo dan Detikx - Rahman, Khairul Arief; Laily, Hamidah Izzatu (Universitas Islam Malang, 2021)
Coverage of the Coronavirus or Covid-19 in Indonesia was accompanied by confusion of information which resulted Mass Hysteria. Media criticism is also present as the vanguard of social control, which is not only limited to what and how it appeared, but also critically explores readiness from the political level of government to the social life of the affected community. How two